Evaluation of a polyclonal antibody for the detection and identification of ranaviruses from freshwater fish and amphibians - Cinkova, Katerina; Reschova, Stanislava; Kulich, Pavel; Vesely, Tomas (Diseases of aquatic organisms, 2010)
A rabbit polyclonal antibody (PAb) raised against European catfish virus (ECV; isolated from black bullhead Ameiurus melas in France) was produced and then evaluated using a panel of 9 ranavirus isolates collected from different lower vertebrate species originating from Australia, North and South America, Southeast Asia, and Europe. Using ranavirus-infected epithelioma papillosum cyprini (EPC) cell cultures, the specificity of the PAb was determined by Western blot, immunogold electron microscopy, and direct enzyme-linked immunosorbent assay (ELISA). Western blot analysis demonstrated that the PAb reacted strongly with a protein with a molecular weight corresponding to approximately 49 kDa. Immunogold electron microscopy provided direct evidence that the epitopes recognized by this PAb were located on the outer surface of virions. The PAb was used for the preparation of a peroxidase-labeled conjugate for the direct ELISA detection of ranaviruses in infected EPC cell cultures. The specificity of the conjugated PAb was tested using ranaviruses, some representative fish viruses of the genera Rhabdovirus and Birnavirus, and samples from various non-infected fish species. The PAb detected all tested ranaviruses except for 2 Santee-Cooper ranaviruses. The direct ELISA enabled the detection of ranavirus from a concentration of 10(3.5) to 10(3.8) TCID50 ml(-1) cell culture. The results of this study revealed that the rabbit PAb raised against ECV could be useful for the development of specific and standardized diagnostic assays for the detection of ranaviruses from freshwater fish and amphibians.
Keywords: obojživelníci; protilátky virové; Animals; Enzyme-Linked Immunosorbent Assay; Rabbits; králíci; zvířata; ELISA; Antibodies, Viral; Fishes; Ranavirus; Amphibians; ryby